PREVALENCE AND CLINICAL FORMS OF MALARIA AMONG FEBRILE HIV-INFECTED CHILDREN SEEN AT USMANU DANFODIYO UNIVERSITY TEACHING HOSPITAL, SOKOTO, NIGERIA - Amodu-Sanni, Maryam Shuaibu; H, Ahmed; NM, Jiya; T, Yusuf; UM, Sani; KO, Isezuo; MO, Ugege; A J, Mikailu (African Journal of Infectious Diseases (AJID), 2020)
Background: Malaria and HIV infections are major health problems facing the world today. Sub-Saharan Africa with 10 percent of world’s population harbors more than half the burden of the scourge. The present study determined the prevalence and clinical forms of malaria among febrile HIV-infected children aged 3months to 15years, seen in Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto, Nigeria. Materials and Methods: Cross-sectional study among febrile HIV-infected children and their control cohort were carried out between May and October 2016. The participants had the following investigations: malarial parasite, packed cell volume, random blood sugar, retroviral test. Results: A total of 140 febrile HIV-infected children aged 3 months to 15 years and 140 febrile HIV-negative age- and gender-matched children were recruited; 100 of the HIV-infected children were on ART and cotrimoxazole. The prevalence of malaria among the febrile HIV-infected children was 71.4% (100/140) which was significantly lower than the prevalence of 94.3% (132/140) among the control group (χ2 27.72, p=0.001). Among the febrile HIV-infected children that had malaria, 54(54.0%) had uncomplicated malaria while 46(46.0%) had severe malaria. Of the 132 controls that had malaria, 48(36.4%) had uncomplicated malaria and 84(63.6%) had severe malaria (χ2 =7.184, p=0.007). Conclusion: Malaria is a problem in HIV-infected children. Since nearly half of the febrile HIV-infected children had severe form of malaria, it is recommended that health promotion, intermittent malaria prophylaxis, early diagnosis and prompt effective treatment should be instituted for HIV-infected children. This may prevent severe form of malaria and its attendant mortality.